2016
DOI: 10.1093/cid/ciw815
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness and Safety of Standard-, Medium-, and High-Dose Daptomycin Strategies for the Treatment of Vancomycin-Resistant Enterococcal Bacteremia Among Veterans Affairs Patients

Abstract: High-dose daptomycin was associated with improved survival and microbiological clearance in VRE-BSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(95 citation statements)
references
References 42 publications
4
89
0
Order By: Relevance
“…However, ID specialist consultation has previously been associated with improved clinical outcomes in other Gram-positive BSIs, perhaps due to more diligent and aggressive source identification and control (24,25). In a recent analysis of hospitalized VA patients with VRE-BSI treated with daptomycin, ID specialist consultation was also independently associated with improved survival (26). We believe future analyses of VREF-BSI should consider the potential influence of ID consultation on clinical outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…However, ID specialist consultation has previously been associated with improved clinical outcomes in other Gram-positive BSIs, perhaps due to more diligent and aggressive source identification and control (24,25). In a recent analysis of hospitalized VA patients with VRE-BSI treated with daptomycin, ID specialist consultation was also independently associated with improved survival (26). We believe future analyses of VREF-BSI should consider the potential influence of ID consultation on clinical outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…It is also reported that daptomycin has an adverse effect concerning creatinine phosphokinase (CPK) elevation . To date, the safety of daptomycin treatment has been widely investigated in relation to various types of infections and pathogens . Although a few reports describe the higher risk of CPK elevation in high‐dose treatment, almost all other previous reports demonstrated the safety of daptomycin treatment with a low or no significant incidence of CPK elevation or other adverse effects, even with high‐dose treatment .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…As a bactericidal agent, it has a potential advantage as a treatment option for deep‐seated infections such as infective endocarditis. Daptomycin dosing for enterococcal infections is variable, and recent data suggest that higher doses may be beneficial for invasive VRE infections . Due to variability in dosing, frequently used regimens for daptomycin, along with other antimicrobial agents commonly used to treat enterococcal infections, are summarized in Table .…”
Section: Currently Available Anti‐vre Antibiotics and Resistancementioning
confidence: 99%
“…Several in vitro studies and limited clinical data have demonstrated that reduced daptomycin susceptibility is attributable to suboptimal dosing and potential mutations in isolates with daptomycin MICs in the 3–4 μg/ml range . In vitro pharmacokinetic/pharmacodynamic (PK/PD) dose response experiments have demonstrated that daptomycin at a minimum of 8 mg/kg/day is required for sufficient bactericidal kill, and 10 mg/kg/day maybe needed to prevent the emergence of resistance in high‐inoculum infections caused by VRE faecalis and faecium . Recently, a multicenter retrospective cohort study that included 62 E. faecium bloodstream infections showed that initial isolates with elevated daptomycin MICs at 3–4 μg/ml were predictive of microbiologic treatment failure with daptomycin and suggested that the current CLSI susceptibility breakpoint for enterococci should be reevaluated …”
Section: Currently Available Anti‐vre Antibiotics and Resistancementioning
confidence: 99%
See 1 more Smart Citation